Social ties & firm performance in emerging markets. (c2019) - Samhoun, Saoud (2019)
Because of the contradicting results in several studies, it is time to perform a Metaanalysis of the effect of social ties on firm performance that has been tested in emerging markets. In particular, I am interested to study boundary conditions of the relationships among the variables that have been used in the studies in the last 20 years. Metaanalytical techniques are used to test the empirical findings and evidences. I test the effects of weak legal and institutional systems in emerging markets on the firm performance. I also examine how the low levels of control and the difficulty in monitoring allow managers to expropriate the informal economy. Finally, I test additional moderators that enhance the relationship between social ties and the firm performance.